FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN ANTENATAL CARE DI PUSKESMAS PASIR PANJANG KOTA KUPANG. - petrus iman tamelab; Theresia Mindarsih; Balbina Antonelda M Wawo (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2021)
Period of pregnancy is a period, that is very prone to health problem, both the health of the mother and thr fetus, so that during pregnancy it is neressary to check regularly in order to avoid distractions as early as possible, from anything that endangers the health of the mother an the fetus she is carrying.Antenatal Care (ANC) is a form of screening, health of problems in mother and fetus. This study aims to analyze the factors associated with the utilization Pasir Panjang Puskesmas, Kupang. The study design used was a quantitative study with a cross sectional approach. Sampel of 58 respondents of pregnant women who are in the Pasir Panjang Puskesmas, Kupang from January until August 2020. The instrument used was a questionnaire. Dara analysis using the chi square test at the level of significance a=0,05. The results showed that there was a relationship between knowledge, husband’s support and the use of antenatal care and there is no relationship between age and distance. Researchers suggest that pregnant woman can play an active role in utilizing health service property so that they can reduce maternal and child mortality Key words: Antenatal Care, age, knowledge, distance, facilities husband’s support.